A reflection on the role of genetics in the concept of “epileptic encephalopathy”, as emerged from the most recent ILEA classification of epilepsy - Angelo Russo; Giuseppe Gobbi (Italian Journal of Pediatrics, 2020)
Abstract The International League Against Epilepsy (ILAE) has been working to standardize the epilepsy classifications for over a hundred years. The latest epilepsy classification has been recently carried out with a careful overview on several topics including the “epileptic encephalopathies” concept and several constructive discussions on this topic have taken place in the international community of epileptologists. Here we wish to share our reflection on a statement of the ILAE commission on the “epileptic encephalopathy” concept, which in our opinion pays less attention to the “electroclinical syndromes” concept in favor of the new and very rapid genetic advances, thus generating confusion. Our aim is both to preserve the role of electroclinical syndromes, while allowing for the association of the phenotype with specific gene mutations, and to underline the importance of bringing electroclinical syndromes back to the forefront of epileptology. We believe the “match” is still open and for this reason we would like to share our considerations and to open a constructive debate on the “epileptic encephalopathy” concept.